Platelet Count, Antiplatelet Therapy and Pulmonary Embolism-A Prospective Study in Patients with Hip Surgery - Monreal, Manuel; Lafoz, Elena; Roca, Jaume; Granero, Xavier; Soler, Josep; Salazar, Xavier; Olazabal, Angel; Bergqvist, David (Thrombosis and Haemostasis, 1995)
Pulmonary embolism (PE) is a serious complication following hip surgery. Trials of antiplatelet thromboprophylaxis indicated a substantial reduction in PE rate, and we prospectively studied the effect of a combination of low-dose heparin and two different antiplatelets. Furthermore, our experience in previous studies suggested that platelet count (PC) levels could be useful to reliably suspect PE at a very early stage, and we prospectively tried to confirm our previous findings.Ours is a prospective study in 459 consecutive patients operated on because of hip fracture (265) or elective hip replacement (194), aimed to determine: 1) whether the benefits of antiplatelets plus heparin on PE outweigh the risks; 2) to assess the clinical usefulness of PC monitoring in these patients, so as to confirm whether PE could be recognized early.It was a prospective, randomized, double-blind study. All patients received unfractioned heparin (7500 IU sc twice daily, starting 2 h before operation). In addition, they received aspirin (200 mg thrice daily, with meals), Triflusal (300 mg thrice daily, with meals), or placebo. Real time B-mode ultrasonography (US) was performed on all patients on the 8-9th day after surgery. Venography was performed in patients with normal US, if clinical symptoms suggested venous thrombosis.Twelve out of the 459 patients (2.6 %) had to discontinue prophylaxis, because of major bleeding (6 patients), or gastric intolerance (6 patients). There were no significant differences between groups in either deep vein thrombosis (26 patients (18 %) with aspirin, 18(12%) with Triflusal, 26 (17 %) with placebo), or PE development (7 patients (5 %) with aspirin, 3 (2 %) with Triflusal, 8 (5 %) taking placebo). By contrast, patients taking aspirin needed significantly more units of blood during the perioperative period, as compared to those taking either Triflusal or placebo (0.36 ± 1.02 vs 0.15 ± 0.47, and 0.16 ± 0.56, respectively; p < 0.05). Otherwise, patients taking Triflusal experienced more commonly nausea and vomiting, as compared to the remaining two groups.But our most important finding was that the 19 patients who subsequently developed PE had mean PC levels significantly lower during the postoperative period. But differences had already been found in the pre-operative count: 189 ± 45 vs 232 ± 76 × 109 liter-1; p = 0.013. According to pre-operative PC levels, PE was present in 8/20 DVT patients (40 %) in the lowest quartile of PC, 7/20 DVT patients (35 %) in the second quartile, 3/20 DVT patients (15 %) in the third quartile, and in 1/15 DVT patients (6.5 %) in the higher quartile. In other words, and after excluding DVT patients with an indeterminate lung scan, 15/230 patients (6.6 %) in the lowest two quartiles developed postoperative PE, as compared to 4/229 patients (1.7 %) in the two highest quartiles (p = 0.009, Chi-Square Test; Odds ratio 3.9; 95 % Cl: 1.2-16.5). The adjusted odds ratio associated to an increase of 50 × 109 platelets × liter-1 was 0.55.